Occupational exposure to Noise and Heat in Plastic Factory in the Industrial City in Jeddah - Al-Jallab, Ahmed Mohammed; Summan, Ahmed Saleh; Balkhyour, Mansour Ahmed (Journal of medical and pharmaceutical sciences, 2020)
This study evaluated some of the occupational hazards present in a plastic factory in Jeddah، Saudi Arabia، which accompanies the manufacturing process. This study aims to assess the level of exposure to noise intensity and heat stress for workers in the work environment during daily working hours، Measurements were performed daily for a period of four months. The researcher unloaded and analyzed the data with the appropriate statistical treatment using SPSS program. The results of the study showed that the average level of noise intensity ranges from (85.6 - 93.3 dB). Average of exposure to heat intensity (30، 57-31، 97) ° C. The study concluded that some of the workers in the factory are at risk of exposure to some occupational hazards such as increased noise intensity، and increased intensity of thermal stress exceeding the permissible exposure limits، according to the standards of the American Conference of Governmental Industrial Hygienists (ACGIH) and the National Institute for Occupational Safety and Health (NIOSH). The researchers of this study provided recommendations and appropriate solutions to protect workers from the risks of the work environment، including the importance of wearing personal protective equipment، environmental assessment and periodic medical examination.